ANALISA KUALITAS PELAYANAN, KEPERCAYAAN DAN KEAMANAN TERHADAP TINDAKAN PEMBELIAN PRODUK SECARA ONLINE - Indah Handaruwati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
This study will examine the Analysis of Service Quality, Trust and Safety of Online Purchasing Actions. The purpose of this research is to find out how far the role of service quality, trust and security will be in online purchasing and to provide an overview of consumer behavior when considering making a purchase. This study uses a questionnaire as a research instrument to obtain data from consumers who make online purchases with a total sample of 30 people. The analysis tool that will be used is Multiple Linear Regression to test the effect of the independent variable on the dependent variable. The results of the multiple linear regression equation are obtained Y = 0.256 0.613+ 0.115+ e Based on the regression equation, the variables of Service Quality, Trust and Safety all have an influence on Online Purchasing Actions. Results of the F-test. From testing using the F test, it was found 76.513. This figure means that the effect of Service Quality, Trust and Security on Online Purchasing Actions is 76,513. Meanwhile, from the results of the t test there is a relationship between service quality factors of 4,657, security of 6,628, and trust of 4,751. Of the three factors, the security factor is the dominant influence. Keywords: Quality of service, Trust, Security and Online Purchasing Actions